Pengaruh Keperilakuan Organisasi Terhadap Kegunaan Sistem Akuntansi Keuangan Desa (Studi Kasus Pada Desa Di Kecamatan Wawonii Selatan) - Wahiatun Adilla Bacia, Ahmad Hamid, Dian Mayafaty Rauf (Jurnal Ilmu Sosial Dan Pendidikan, 2024)
This research aims to determine the influence of Training, Clarity of Goals and Support from Superiors, which partially and simultaneously have a significant effect on the Usefulness of the Village Financial Accounting System in case studies in South Wawonii District, Konawe Islands Regency, Southeast Sulawesi Province. The type of research used is a quantitative approach. Data was collected using the questionnaire method in the form of statements measured using a Likert scale. The data analysis technique used is the multiple linear regression test using SPSS Version 29 tools. The sample in this study was 30 people who were related to the village financial system. The results of this research show that the variables Training, Clarity of Goals and Support from Superiors have a partial and significant effect on the usefulness of the village financial accounting system. The variables Training, Clarity of Goals and Support from Superiors also simultaneously influence the usefulness of the village financial accounting system.